Una aproximación al juramento estimatorio (2019)
This paper determines the main characteristics of the pledge analyzing constitutionality judgments made in respect of Article 206 of the General Procedural Code; specified the nature of the institution as a requirement of the claim and the plea, as a piece of evidence, as a parameter for imposing sanctions, and establishes its relation with the principle of congruence; the requirements of the pledge; scenarios of application in civil law; and finally alludes to the sanctions and the possibilities of interpretation around its imposition and quantification, in order to establish how the sanction should be quantified under the principle of favorability.